On Computation and Analysis of Topological Index-Based Invariants for Complex Coronoid Systems - Muhammad Aamer Rashid; Sarfraz Ahmad; Muhammad Kamran Siddiqui; Mohammed K. A. Kaabar (Complexity)
In chemical graph theory, benzenoid systems are interrogated as they exhibit the chemical compounds known as benzenoid hydrocarbons. Benzenoid schemes are circumscribed as planar connected finite graphs having no cut vertices wherein the entire internal sections are collaboratively congruent regular hexagon. The past couple of decennium has acknowledged an extravagant development regarding implementation of information theoretic framework in miscellaneous ramification of science, for instance, in social sciences, biological, physical, and engineering. Explicitly, this tremendous improvement has been outstanding in the field of soft computing, molecular biology, and information technology. The information theory, delineated by Claud Shannon, has no less importance when it was considered. Shannon put forwarded the apprehension of entropy to enumerate upper bounds in transmission rates in telephonic channels, in optical communication, and in wireless. The prestigious feature of entropy is that it entitles the amount of uncertainty in a system. The substantial participation of this paper is to explore characteristics of graph entropies and then keep moving forward to talk about the formation of coronoid polycyclic aromatic hydrocarbons. Likewise, we estimate entropies through precise topological indices established on degree of terminal nodes.